ANALISIS PENGENDALIAN KUALITAS PRODUK PADA GRIYA KRIPIK TEMPE - Aisyah, Nur; Nofriani Fajrah (LPPM Universitas Putera Batam, 2024)
Competition in the food Industry, is not only on the scale of the output production or brand, but also on the quality of products produced. The company needs to take quality control measures to maintain the quality of their products to comfrom to the quality standards set by the company, so that their products can be accepted by consumers. Griya Kripik Tempe is a company in the food which in the production process the are still various and fluctuating defects.The purpose of this study was to identify the level of variation in defects in the production process, identify the level of quality control performance by finding the value of DPMO, and tools design of cutting with of QFD method, fishbone diagrams are used to identify the causes of defects. The results showed that there no data out of control limits by p-chart,this value is still relatively low. Based on the fishbone diagram, it was found that human, machine, method, material and environmental factors were the cause of defects in kripik tempe production. The result of designing a cube-shaped tempe cutting tool, with many blades, a lever for pressing and a container for pieces of tempe.